The Effect of Lime Stone in the Probability of Formation Pores Structures in Glass Ceramic Based on Scoria Basalt Rocks - Birawidha, David Candra; Sumardi, Slamet; Oktaviando, Fany; Karo-Karo, Pulung; Isnugroho, Kusno; Hendronursito, Yusup; Amin, Muhammad (JST (Jurnal Sains dan Teknologi), 2023)
This paper provides a Lightweight material is the result of technological problems in increasing the efficiency of finished products, saving manufacturing costs and environmentally friendly technology by reducing the amount of material used. There are many kinds of material manufacturing technology, ranging from the use of lightweight materials from the start, combining materials into composites and modifying the structure and characteristics of the material to make it lightweight. One commonly used method is to mix glass-ceramic with a foaming agent in purpose to modify the structure of material. The purpose of this study is to utillize basalt rock as source of glass ceramic and mixed with limestone to form cellular structure with optimal composition. The samples was crushed and sieve through 100 mesh afterward all material is mixed varied between basalt and lime with a ratio of sample A (100% Basalt), sample B (3:7), sample C (5:5), and sample D (7:3), which were burned at a temperature of 1100°C and 1300°C. After all sample reach designated temperature, all sample undergo annealed cooling in the furnace. Based on the characterization results, the best glass-ceramic sample formed with pores structure formation was sample B which is 70% addition of limestone in basalt mixture and burned at a temperature of 1100°C with a total pore size of 63% and a density of 0.92 g/cm3, where the glass-ceramic structure detected pyroxene and lime phases with a SiO2 composition of 14.61%. Basalt cellular ceramic is obtained in optimal condition with low density and higher percentage porosity.